SOCIAL SUPPORT NETWORKS IN CARE FOR THE PERSON WITH A MENTAL DISORDER: REFLECTIONS - Daiana Foggiato de Siqueira; Mariane da Silva Xavier; Andreivna Kharenine Serbim; Marlene Gomes Terra (Universidade Federal de Santa Maria, 2018)
Aim: to reflect on the formal and informal social support networks in the care for the person with mental disorder centered on the psychosocial paradigm. Method: a theoretical-reflective study based on the epistemological Brazilian Psychiatric Reform, which redirects the care model in mental health. Results: the family is the primary source of social network resource in informal support and is sometimes the key to the effectiveness of the care provided by the formal social support network. It is important that the services develop support a strategy so that the person with mental disorder and his/her family can clarify his/her doubts and minimize the challenges that cover mental health care. Conclusions: the social support network is an aspect that needs to be valued by the health professional, since it enables mental health care planning.